Deteksi Kerusakan Pada Struktur Membran Dengan Menggunakan Sinyal Suara - Febri Feridianto; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Structural Health Monitoring (SHM) is a process of identifying damage by Nondestructive Evaluation (NDE). The flexible and lightweight membrane properties cause testing methods that require contact between the sensor and the specimen can not be performed. The method can be done by non-contact method. In this study a non-contact method was proposed to monitor the membrane by utilizing the sound signal as an excitation. This method has the advantage because it is not costly to set-up testing. Recorded data in the form of time domain is transformed into a frequency domain using FFT (Fast Fourier Transform) method. With the domain data frequency response and domain data excitation frequency can be processed into data FRF (Frequency Response Function). FRF in matrix form is used to estimate the mode shape. The first natural frequency of the mode shape is transformed using a 2D-CWT wavelet to detect the location of the damage. The study was performed on membranes under normal and damaged conditions. The research was done by experiment. The results of the research show that the proposed method can detect the location of the damage properly and accurately.Keywords: SHM, Membrane, Signal Sound, FFT, FRF, Mode Shape